Results of Brown Bullhead Fingerling Rearing in Recirculating Fish Production Systems - Vinginder, Csaba (Acta Agraria Debreceniensis, 2005)
Predator fish species are in great demand, both in fish production and consumption. Because of their rarity and perfect meat quality, these species have considerable economical significance and increasing domestic and foreign demand. The brown bullhead (Ictalurus nebulosus) has been in Hungary for more than 100 years, but not popular because of its early maturation rate, aggressive reproduction and slow growth. Despite of these properties, larger specimens (about 150-200 g) are marketable overseas. Our objective is to ensure the adequacy of the brown bullhead in intensive fish farming and its biological, technological and economic references. The pre-experiments were performed at the Bocskai Fishing Co-operative in Hajdúszoboszló, where we reared the juvenile age class. In our university’s recirculating system we examinated the brown bullhead from the fingerling age class. The black bullhead prefers artificial feed, and produces excellent growth parameters and a specific feed-live weight conversation ratio.